1991
DOI: 10.3109/00365599109107952
|View full text |Cite
|
Sign up to set email alerts
|

Values of Intact Serum Parathyroid Hormone in Different Stages of Renal Insufficiency

Abstract: Intact serum parathyroid hormone (PTH) values were determined in 136 patients consulting the out-patient clinic for renal medicine and in 36 patients on maintenance hemodialysis in order to reveal the extent of parathyroid involvement in different stages of renal insufficiency. Elevated PTH values were found in 53 of the conservatively treated patients and in all but 4 of those on hemodialysis. Serum creatinine values and the duration of uremia correlated significantly to serum PTH, and multivariate analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…After being thawed, 110 µL of the concentrated solution was pipetted into the chemostat containing 2 L of the buffer, giving a final concentration of 1100 pg/mL. This initial condition was set according to clinical studies by Hellman et al 14 and Liu et al 15 The former reported values of intact serum PTH (iPTH) from 100 to 1000 pg/mL for patients in various stages of renal insufficiency. The latter found an average iPTH concentration of ∼1500 pg/mL in chronic renalfailure patients prior to blood purification.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…After being thawed, 110 µL of the concentrated solution was pipetted into the chemostat containing 2 L of the buffer, giving a final concentration of 1100 pg/mL. This initial condition was set according to clinical studies by Hellman et al 14 and Liu et al 15 The former reported values of intact serum PTH (iPTH) from 100 to 1000 pg/mL for patients in various stages of renal insufficiency. The latter found an average iPTH concentration of ∼1500 pg/mL in chronic renalfailure patients prior to blood purification.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Derangements in calcium homeostasis occur early in renal insufficiency, and patients receiving renal transplants suffer from variable degrees of hyperparathyroidism (HPT) [1,2]. The mechanisms contributing to the development of secondary HPT are complex and incompletely clarified [3,4].…”
mentioning
confidence: 99%